Cardiovascular autonomic dysfunction predicts increasing albumin excretion in type 1 diabetes. Issue 3 (24th November 2017) - Lu, Liangjian; Marcovecchio, M Loredana; Dalton, R Neil; Dunger, David
Abstract : Objective: To determine the potential role of cardiovascular autonomic dysfunction in the development of renal complications in young people with type 1 diabetes (T1D). Methods: In this prospective study, 199 children and adolescents recruited to the Oxford Regional Prospective Study underwent assessment of autonomic function ~5 years after diagnosis, and were subsequently followed with longitudinal assessments of HbA1c and urine albumin‐creatinine ratio (ACR) over 8.6 ± 3.4 years. Autonomic function was assessed with 4 standardized tests of cardiovascular reflexes: heart rate (HR) response to (1) Valsalva Maneuver, (2) deep breathing, (3) standing, and (4) blood pressure (BP) response to standing. Linear mixed models were used to assess the association between autonomic parameters and future changes in ACR. Results: Independent of HbA1c, each SD increase in HR response to Valsalva Maneuver predicted an ACR increase of 2.16% [95% CI: 0.08; 4.28] per year ( P  = .04), while each SD increase in diastolic BP response to standing predicted an ACR increase of 2.55% [95% CI: 0.37; 4.77] per year ( P  = .02). The effect of HR response to standing on ACR reached borderline significance (−2.07% [95% CI: −4.11; 0.01] per year per SD increase, P  = .051). Conclusions: In this cohort of young people with T1D, enhanced cardiovascular reflexes at baseline predicted future increases in ACR. These results support a potential role for autonomic dysfunction in the pathogenesis of diabetic nephropathy.